Online Education Adaptability for South African Learners with Dyscalculia and Dyslexia using Digital Learning Methods - Winiswa Mavutha; Aradhana Ramnund Mansingh (Clinical Sociology Review)
The United Nations Sustainable Development Goal 4 defines equal and inclusive education. Countries of the global south, including South Africa, have several interventions to achieve before making headway on this goal. South Africa has a unique political and historical narrative, and almost three decades post-apartheid, there remain stark differences in school and post-school education. Amongst some of these include learners with learning disabilities. This research focuses on learners with learning disabilities, such as Dyscalculia and Dyslexia. The introduction of digital technologies within higher education institutions excludes these learners as the adaptability of digital learning techniques has not been considered for specific learning disabilities. The challenges are now heightened. Although primary studies have been conducted in the past, no definitive solutions have been established for the seamless integration of these learners into mainstream education. Hence a different research approach was undertaken.  An expansive review of existing scholarship was conducted using online academic resources and search platforms such as Google Scholar, Scopus and EBSCOhost. The purpose was to engage with a wide range of national and global literature. A discussion and comparison of available resources and tools were outlined and structured according to the inclusion and exclusion criteria. The study was underpinned by the universal design for learning theory. Global research indicated the availability of online tools that were too expensive for South African education and incompatible with the lack of skills and infrastructure. The literature provided adequate information to develop an introductory clinical sociology intervention and embark on a process of awareness and support for educators and affected learners